ANALISIS TERHADAP FAKTOR-FAKTOR YANG MEMPENGARUHI DALAM OPTIMALISASI PENERIMAAN PAJAK - Suhono, Suhono (Program Studi Akuntansi, Universitas Kuningan, 2017)
Problems in this study are related to the efforts taken to increase tax revenue optimization. One the most important factors that can be done is related to society learning aspect stimulating their compliance to paying taxes. This plays significant role in optimizing tax revenue. The method used in this research are qualitative method. This method allows us to obtain a description of strategic factors formulation which plays role in the optimization of tax revenue. This research is also conducted by using literature study and referring to previous research results which are associated to the regulation of taxation in Indonesia. The results of this research show that strategic factors play important roles in the optimization of tax revenue in the forms of the tax administration, the productivity of the tax authorities, the concept of taxation, as well as tax subjects compliance. The results also recommend the implementation of educational elements in decision-making, work environment, and human resources quality in the efforts to promote a tax positive image which can be obtained through 1) productivity empowerment and a conducive working environment, 2) tax services administration satisfaction, and 3) empowerment, independence and well-being aspects implementationon the concept of taxation.Keywords: Learning, Compliance, Tax Revenue